NARASI HADIS TENTANG KEUTAMAAN BULAN DZULHIJJAH DALAM DAKWAH DIGITAL: ANALISIS KONTEN SHORTS YOUTUBE USTADZ MUHAMMAD NUZUL DZIKRI - Manik, Zulfirman; Reza, Fadhila; Ibrahim Sihite, Andy; Panjaitan, Mawardah; Pratama Maulana, Septian (UIN Sumatera Utara Medan, 2025)
The advancement of digital da'wah across various social media platforms has led to a fundamental shift in how Islamic teachings are communicated, particularly through short-form video formats such as YouTube Shorts, which have become increasingly popular among contemporary internet users. This format allows religious messages to be delivered rapidly, concisely, and in highly accessible ways, requiring preachers to adapt their communication methods to the fast-paced and visually driven nature of digital media. In this context, it is essential to examine how hadith-based Islamic narratives are constructed, formulated, and adapted within media formats that are extremely limited in duration yet demand clarity and audience engagement. This study aims to analyze the construction of hadith narratives on the virtues of the month of Dhu al-Hijjah in the YouTube Shorts content produced by Ustadz Muhammad Nuzul Dzikri, focusing on hadith selection, presentation patterns, rhetorical strategies, and their potential influence on audience comprehension. The study employs a qualitative approach using content analysis, with data obtained through participant observation, documentation, and in-depth analysis of several relevant videos. The findings indicate that Ustadz Muhammad Nuzul Dzikri effectively constructs the narrative on Dhu al-Hijjah's merits by selecting authentic hadiths, presenting them thematically, and employing communicative, concise, and audience-friendly language. This adaptation demonstrates that Islamic scholarly authority can be integrated efficiently into digital da'wah formats aligned with modern media consumption behaviors.